Bioresources technology in sustainable agriculture : biological and biochemical research - Abdullah, Mohamad Faiz Foong; Ali, Mohd Tajudin Bin Mohd; Yusof, Farida Zuraina M. (Apple Academic Press, 2018)
This book focuses on cutting-edge advances and applications in tropical agriculture and bioresources. It outlines some of the newest advances, basic tools, and the applications of novel approaches to improve agricultural practices and utilization of bioresources for the enhancement of human life. Highlights include a thorough discussion on various aspects of agricultural modernization through technological advances in information technology, efficient utilization of under-exploited natural bioresources, new chemical approaches for the generation of novel biochemicals, and the applications of forensic and genetics approaches for bioresource conservation.